2016
DOI: 10.1590/0100-29452016229
|View full text |Cite
|
Sign up to set email alerts
|

INTEGRAL UTILIZATION OF SERIGUELA FRUIT (Spondias purpurea L.) IN THE PRODUCTION OF COOKIES

Abstract: -This study aimed to process, characterize and use seriguela fruit residue pulp and flour (Spondias purpurea L.) (SFR) in the processing of cookies, evaluating nutritional and microbiological quality and sensory acceptance. SFR was prepared and characterized as to its physical and chemical characteristics. Cookies made with SFR at concentrations of 0, 10, 20 and 30% were submitted to analyses of chemical composition, acidity, pH, ascorbic acid, water activity, in addition to yield and costs. Microbiological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
1
9
0
3
Order By: Relevance
“…Previous studies have found high amounts of fibre in guava peel flour (15.24%) and siriguela flour (12.82%). However, the fibre content in these was lower than that found in OGF (Bertagnolli et al ., ; de Albuquerque et al ., ). As such, this fraction shares many of the characteristics and benefits attributed to dietary fibre in the human body.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have found high amounts of fibre in guava peel flour (15.24%) and siriguela flour (12.82%). However, the fibre content in these was lower than that found in OGF (Bertagnolli et al ., ; de Albuquerque et al ., ). As such, this fraction shares many of the characteristics and benefits attributed to dietary fibre in the human body.…”
Section: Resultsmentioning
confidence: 97%
“…Quando comparadas a outros estudos farináceos, podemos observar que Costa et al (2017) obtiveram pH 4,16 para farinha do mesocarpo do fruto do pequizeiro. Já no estudo realizado por Albuquerque et al (2016) com pH 3,17 para a farinha dos resíduos de seriguela. Estes autores obtiveram resultados de pH inferiores aos obtidos neste estudo para as farinhas do fruto de H. stigonocarpa.…”
Section: Resultsunclassified
“…Os valores de vitamina C forram semelhantes aos encon-trados por Albuquerque et al, (2016), em cookies adicionados de seriguela. Em sua formulação controle (sem adição da seriguela), os autores encontraram um valor de 5,08mg/100g de vitamina C e 8,96 até 14,15 para os adicionados de seriguela.…”
Section: Resultsunclassified
“…Segundo Amácio et al, (2014), os polifenóis são poderosos antioxidantes, e no pólen são encontrados diversos tipos, dentre eles os flavonoides. Essa variedade de polifenóis é dada pelos inúmeros grãos diferentes que podem ser encontrados no pólen, que aumenta ainda mais seu poder antioxidante.…”
Section: Resultsunclassified